Human neural tissue sources and surgical sample-collecting methods - Gradišnik, Lidija (Surgery and surgical endoscopy, 2022)
The techniques of cell isolation supported by modern laboratory procedures have been rapidly progressing, offering a wide range of in vitro research opportunities. The first and one of the most important steps in cell isolation is tissue harvesting, which is most commonly performed during surgical procedures. This is the basis that determinates the success of isolation. This article describes human neural tissue sources and neurosurgical ap- proaches to tissue collection.
Keywords: celične kulture; nevralno tkivo; nevrokirurgija